Stem cell-based therapy in periodontal regeneration: a systematic review and meta-analysis of clinical studies - Liang Sun; Xinya Du; Huifang Kuang; Honglan Sun; Wen Luo; Chao Yang (BMC, 2023)
Abstract Background Periodontitis is a common and chronic inflammatory disease characterized by irreversible destruction of the tooth surrounding tissues, especially intrabony defects, which eventually lead to tooth loss. In recent years, stem cell-based therapy for periodontitis has been gradually applied to the clinic, but whether stem cell-based therapy plays a positive role in periodontal regeneration is unclear at present. Methods The clinical studies related to the evaluation of mesenchymal stem cells for periodontal regeneration in PubMed, Cochrane Central Register of Controlled trials (CENTRAL), Web of Science (WOS), Embase, Scopus, Wanfang and China national knowledge infrastructure (CNKI) databases were searched in June 2023. The inclusion criteria required the studies to compare the efficacy of stem cell-based therapy with stem cell free therapy for the treatment periodontitis, and to have a follow-up for at least six months. Two evaluators searched, screened, and assessed the quality and the risk of bias in the included studies independently. Review Manager 5.4 software was used to perform the meta-analysis, and GRADEpro GDT was used to evaluate the level of the evidence. Results Five randomized controlled trials (RCTs) including 118 patients were analyzed. The results of this meta-analysis demonstrated that stem cell-based therapy showed better therapeutic effects on clinical attachment level (CAL) (MD = − 1.18, 95% CI = − 1.55, − 0.80, P < 0.00001), pocket probing depth (PPD) (MD = − 0.75, 95% CI = − 1.35, − 0.14, P = 0.020), and linear distance from bone crest to bottom of defect (BC-BD)( MD = − 0.95, 95% CI = − 1.67, − 0.23, P = 0.010) compared with cell-free group. However, stem cell-based therapy presented insignificant effects on gingival recession (P = 0.14), linear distance from cementoenamel junction to bottom of defect (P = 0.05). Conclusion The results demonstrate that stem cell-based therapy may be beneficial for CAL, PPD and BC-BD. Due to the limited number of studies included, the strength of the results in this analysis was affected to a certain extent. The high‐quality RCTs with large sample size, multi-blind, multi-centric are still required, and the methodological and normative clinical study protocol should be established and executed in the future.